UJARAN KEBENCIAN DALAM DAKWAH: ANALISIS TENTANG PENGEJAWANTAHAN IDE AMAR MAâRUF NAHI MUNGKAR DI KALANGAN PARA DAâI DI KALIMANTAN TIMUR - Ridho, Miftahur (LENTERA: Jurnal Ilmu Dakwah dan Komunikasi, 2018)
Hate speech is among the most vicious problem faced by Muslims in the world. As Muslims are obliged to perform the principle of al amr bi al maâruf wa tanhawna anil munkar (commanding right and forbidding evil), what perceived as hate speech sometimes overlaps such basic tenet of Islamic principle of commanding right and forbidding wrong. The aim of this research is therefore twofold. First, it explore the contruction of hate speech among Daâis (Islamic preachers) in traditional Islamic boarding schools in East Kalimantan. And Seccondly, it explores ideal responses toward such practices as perceived by those Daâis. Findings suggest that the construction of hate speeches and ideal responses towerds it, among Daâis in Islamic traditional boarding schools known as pondok pesantrens, is founded mostly upon the principle of potential damage of those hate speech practices.Keywords: Hate speech, Islamic Daâwa, and Daâis in East Kalimantan.